Mapping of colorectal carcinoma diseases with activation of Wnt/beta-catenin signalling pathway using hierarchical clustering approach. Issue 3 (13th January 2021) - Mosnier, Jean-François; Airaud, Fabrice; Métairie, Sylvie; Volteau, Christelle; Bezieau, Stéphane; Denis, Marc
Abstract : Aims: To map the colorectal carcinoma (CRC) diseases with significant Wnt signalling pathway activation for delineating their clinicopathological and molecular profiles. Methods: Mapping is based on hierarchical clustering analyses of a series of 283 CRCs. Data tabulated were histopathological patterns, immunophenotypic differentiation, RAS, RAF, CTNNB1 mutations and microsatellite instability status, tumour-infiltrating lymphocytes (TILs) and genetic setting. Beta-catenin expression in more than 10% of cell nuclei in the centre of tumour serves as a surrogate marker of significant activation of Wnt signalling pathway. Results: Nuclei beta-catenin expression was present in 95% of CRCs; 56% of them met the criteria of high level of nuclei beta-catenin expression (≥10%). Proportion of beta-catenin positive nuclei was significantly higher in younger patients, rectal and left-sided colonic carcinomas. CRCs with high level of nuclei beta-catenin expression were regrouped into three clusters: (1) microsatellite stability (MSS) CRCs with no constitutive MAPK pathway activation including 90% of low-grade adenocarcinoma, NOS, with intestinal differentiation without TILs; (2) RAS -mutated MSS CRCs including low-grade adenocarcinoma, NOS, with intestinal differentiation and mucinous adenocarcinoma without TILs; (3) MSI-H CRCs including both BRAF -mutated CRCs evolving from serrated pathway and CTNNB1 -mutated CRCs associated with Lynch syndrome. Conclusions: MSS low-grade adenocarcinoma, NOS, with intestinal differentiation without TILs ('crypt-like adenocarcinoma') might be the morphological pending of canonical molecular subtype of CRC defined as displayed molecular epithelial differentiation and upregulation of WNT in consensus molecular classification of CRC.